2005
DOI: 10.1093/rheumatology/keh589
|View full text |Cite
|
Sign up to set email alerts
|

Recurrence risk for psoriasis and psoriatic arthritis within sibships

Abstract: The concordance for psoriasis is greater than for PsA, but the concordance rate for PsA was similar to that in HLA identical siblings with rheumatoid arthritis. There was discordance in pattern of arthritis for most sib pairs. There is no support for the use of more complex classifications of PsA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
42
0
2

Year Published

2008
2008
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 74 publications
(48 citation statements)
references
References 25 publications
4
42
0
2
Order By: Relevance
“…The prevalence of psoriasis in FDRs of probands with PsA was also increased compared with the population control. A recent UK study reported the prevalence of PsA in siblings to be 14.3% and that in the general population to be 0.3% 12. The calculated λ S was therefore 47.…”
mentioning
confidence: 90%
“…The prevalence of psoriasis in FDRs of probands with PsA was also increased compared with the population control. A recent UK study reported the prevalence of PsA in siblings to be 14.3% and that in the general population to be 0.3% 12. The calculated λ S was therefore 47.…”
mentioning
confidence: 90%
“…Both conditions are considered to be complex diseases that are influenced by environmental and genetic factors. The genetic liability towards the susceptibility to PsA, determined using the sibling recurrence risk (λ s ), is estimated to be much higher (λ s > 30) than that of PsV (λ s = 8–12) 24. These differences are suggestive of additional genetic susceptibility loci for PsA, although it is highly likely that environmental factors also contribute to these differences 5…”
Section: Introductionmentioning
confidence: 99%
“…Moll and Wright4 were the first to report a recurrence risk ratio in first-degree relatives (λ 1 ) of 55, compared with estimates ranging from five to 10 in PsC. Another study from the UK, reported a PsA prevalence of 14.3% among siblings and recurrence risk ratio (λ s ) of 47 5. Our group has found a PsA prevalence of 7.6% among first-degree relatives leading to a λ 1 of 30.4 6.…”
mentioning
confidence: 99%